OTITIS MEDIA: RE-EVALUATION OF DIAGNOSIS AND TREATMENT IN PRESENT - Valeriu Popescu (Amaltea Medical Publishing House, 2008)
The changing susceptibility of bacterial otopathogens is only one aspect of the evolving concepts regarding pathogenesis, immunoprophylaxis, pharmacodynamies, and sequelae of acute otitis media that mandates new insights for achieving a successful outcome. 2004 guidelines by the American Academy of Pediatrics for the treatment of acute otitis media provide one perspective that proposes a rethinking of the routine use of antimicrobial therapy with the hope of preventing further increases in bacterial resistance among otopathogens. The goals of this article are to incorporate the advances in diagnosis, treatment, prevention and management of sequelae into strategies that optimize the outcome of acute otitis media and limit further emergence of resistant otopathogens.